Crystal engineered albendazole with improved dissolution and material attributes. Issue 9 (2nd February 2016) - Thakur, Amitha; Thipparaboina, Rajesh; Kumar, Dinesh; Sai Gouthami, Kodukula; Shastri, Nalini R.
Abstract : Spherical agglomerates have shown 5.58 and 5.60 fold increases in AUC and DE, respectively when compared to ABZ at 6 hours. Abstract : Albendazole (ABZ) is a broad spectrum anthelminthic drug and is in the WHO list of essential medicines. It is a "brick dust" drug with very poor water solubility (0.2 pg ml −1 at 25 °C). In the present study, crystal engineering of ABZ was carried out using two different techniques: solvent recrystallization and spherical agglomeration. All the modified habits have shown improved dissolution and flow properties. Spherical agglomerates with HPC as a binder have shown a 5.60 fold enhancement in dissolution efficiency at the end of 6 h when compared to ABZ. The agglomerates with binder showed good compressibility and can be successfully used for direct tabletting.